The Science of "Muddling Through" - Lindblom, Charles E. (Public Administration Review, 1959)
Short courses, books, and articles exhort administrators to make decis ions more methodically, but there has been little analysis of the deci sion-making process now used by public administrators. The usual proce ss is investigated here-and generally defended against proposals for m ore "scientific" methods. Decisions of individual administrators, of c ourse, must be integrated with decisions of others to form the mosaic of public policy. This integration of individual decisions has become the major concern of organization theory, and the way individuals make decisions necessarily affects the way those decisions are best meshed with others'. In addition, decision-making method relates to allocati on of decision-making responsibility-who should make what decision. Mo re "scientific" decision-making also is discussed in this issue: "Tool s for Decision-Making in Resources Planning."